Sintesis 2’-Hidroksi-5’-Kloro-3,5-Dimetoksi-4-Hidroksikalkon - Amanuddin Amanuddin; Hanggara Arifian; Agung Rahmadani; Rolan Rusli (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Chalcone are compounds that have 2 aromatic rings connected by 3 carbon atoms which are an ?, ? unsaturated carbonyl system that have various biological activities. 2'-hydroxy-5'-chloro-3,5-dimethoxy-4-hydroxicalcone was synthesized from 2'-hydroxy-5'-chloro acetophenone and syringaldehyde using a NaOH catalyst. This compound was purified using Column Chromatography by isocratic method using n-hexane:ethyl acetate (15:1) as eluent. This compound has a Rf 0.75 and 2.7% of yield.